Exploring the effects of large-area dorsal skin irradiation on locomotor activity and plasm melatonin level in C3H/He mice. (2nd December 2021) - Fan, Xuewei; Chen, Zeqing; Li, Wenqi; Qin, Haokuan; Huang, Shijie; Lu, Zhicheng; Li, Yinghua; Liu, Muqing
ABSTRACT: As the largest organ exposed to the outside of mammals, skin has direct photosensitivity. Recent studies have even shown that cutaneous irradiation played a role in local circadian systems. However, whether it can further affect the central clock system is controversial. Here, plasm melatonin rhythm of melatonin-proficient C3H/He mice was assessed, and on this basis, a well-designed segmented lighting method was used to investigate the effects of dorsal skin irradiation on locomotor activity and plasm melatonin content in male C3H/He mice. In brief, mice were separately exposed to cutaneous irradiation, intraocular irradiation or darkness for 60 min at specific moments. The results showed that neither blue nor red cutaneous exposure had obvious effect on central rhythm oscillation while intraocular irradiation could significantly change the central clock of mice, and the effect of blue light was more forceful than red light. It suggests that intraocular nonvisual channels still play a dominant role in rhythmic regulation, which has not been challenged by the discovery of local light entrainment in exposed peripheral tissues.